Examining a Novel Method of Earnings Management During Inventory Investment Reduction and Its Relationship with Firm Size and Life Cycle Through the Adjustment of the Modern Capital Structure Theory in the Tehran Stock Exchange and Iran Over-the-Counter - Basati, Ali; Rezaei, Emad; Azinfar, Kaveh; Gholamnia Roshan, Hamid Reza (Management Strategies and Engineering Sciences, 2025)
Previous research has not examined earnings management during inventory investment reduction, nor the impact of capital structure on managed and unmanaged performance. Therefore, the main objective of this study is to investigate novel methods of earnings management during reductions in inventory investment using discretionary and non-discretionary accruals, and to divide performance into two components: (1) managed performance, where the manager has the ability to employ discretionary accruals, and (2) unmanaged performance, where the manager lacks the ability to utilize discretionary accruals. Subsequently, we examined the level of insignificance, which indicates the adjustment of capital structure theories in favor of managers’ opportunistic earnings management. The statistical sample of this research includes 173 companies listed on the Tehran Stock Exchange and Iran Over-the-Counter. The research findings indicate a significant positive relationship between risk, liquidity, and firm size 2, and a negative relationship between leverage and both managed and unmanaged performance. Consequently, due to the lack of a significant relationship between inventory investment, firm size 1, and firm life cycle with managed and unmanaged performance, this indicates that an adjustment has occurred in the capital structure theory, representing opportunistic earnings management. A comparison of the managed and unmanaged performance models in this study revealed that in Iranian firms, when inventory investment decreases, managers reduce liquidity through discretionary accruals, and present firm size 1, firm life cycle, and operational history as increased, and firm size 2 as decreased, to engage in opportunistic earnings management.